Determinants of the Household Electricity Consumption: A Case Study of Delhi - Tewathia, Nidhi (International Journal of Energy Economics and Policy, 2014)
Electricity has attained a very important place in every household on this planet. It is a major contributor towards improvement of the standard of living of any individual, family and society at large. This paper aims to find out the monthly average household electricity consumption and seasonal variations in this consumption for the months of summer, winter and moderate weather for Delhi. The factors which influence the electricity consumption of a household have been examined by using a questionnaire based study of 395 Delhi households selected via stratified random sampling technique. Multiple regression models have been run to describe the pattern of household electricity consumption. The results from the study show that the stock of appliances in a household contributes the most to the variation in the dependent variable. An inverted U-shaped non-linear Temperature-Electricity Curve has been derived from the primary data used in the study. Keywords: Delhi; Electricity; Electricity Consumption; Household JEL Classifications: D11; D12; Q44